Affective Polarisation and Emotional Distortions on Social Media. (October 2022) - Tanesini, Alessandra
Abstract: In this paper I argue that social networking sites (SNSs) are emotion technologies that promote a highly charged emotional environment where intrinsic emotion regulation is significantly weakened, and people's emotions are more strongly modulated by other people and by the technology itself. I show that these features of social media promote a simplistic emotional outlook which is an obstacle to the development and maintenance of virtue. In addition, I focus on the mechanisms that promote group-based anger and thus give rise to affective polarisation. In the final section, after a discussion of the positive value of some forms of anger, I argue that SNSs should not be designed to prohibit or suppress anger, but that its encouragement should also be avoided. I conclude with a suggestion about how this might be achieved.